If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -1y + 7 = 0 Reorder the terms: 7 + X + -1y = 0 Solving 7 + X + -1y = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + X + -7 + -1y = 0 + -7 Reorder the terms: 7 + -7 + X + -1y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + X + -1y = 0 + -7 X + -1y = 0 + -7 Combine like terms: 0 + -7 = -7 X + -1y = -7 Add 'y' to each side of the equation. X + -1y + y = -7 + y Combine like terms: -1y + y = 0 X + 0 = -7 + y X = -7 + y Simplifying X = -7 + y
| -2w+-22=-13+2w-9 | | 10z-4=2(5n+2) | | 2x^2+39x=0 | | 4x=20-4 | | 2x+25=6x-5 | | 8(2x+10)-6x=10 | | N=d-m | | 7x=344 | | 4m^2-24m+36=0 | | x=-y | | -26.25+-15.5=-15.5+-11.78 | | 8a^2-2a^2x^4= | | 5(3n+2)+n=4(4n-7) | | 3x+4-x=6 | | X+(x+1)+(x+2)=138 | | 3x-45+6x=0 | | 6y-2(3+y)=2y+10 | | 2+8-3-12= | | y=-6x^2+7x-21 | | 7(5a+1)-9=a-(a+1) | | (40x+72)-(4-2x)=-9 | | -4(1+8x)-3x=-109 | | 2b^2+12b-24=0 | | 2t+1=8 | | 4x^2+9x-16=0 | | 10x=-120 | | x^2-9x+112=0 | | -15t^2+90t+10=85 | | 31x+58=0 | | x^2+15x=0 | | -5x+-35=-5x+35 | | (4+(-10))x= |